Physicochemical, structure and functional characteristics of Tacca leontopetaloides starches grown in Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Yonata D, Triwitono P, Lestari LA, Pranoto Y. 2023. Physicochemical, structure and functional characteristics of Tacca leontopetaloides starches grown in Indonesia. Biodiversitas 24: 6396-6406. Understanding the physicochemical, structure and functional characteristics of tacca tuber (Tacca leontopetaloides) starch is crucial as a scientific basis for its development, especially in the food industry. Despite the abundance of starch in Indonesian tacca tubers, its potential remains largely untapped. This research aims to determine the physicochemical, structure and functional characteristics of tacca tuber starch from three different regions in Indonesia: Bangkalan, Garut and Sumenep. Wet extraction yielded tacca tuber starch with yields ranging from 21.26 to 26.42%. Significant differences (p
Keywords: Functional, physicochemical, starch, structure, tacca tuber